African women and intellectual leadership
1 online resource.
Keywords: "This book highlights the pioneering roles of African women as leaders and role models in Kenya, providing examples taken from across education, health, business, and a range of other sectors. Drawing on authentic first-hand accounts and narratives from key women in leadership positions, and those who have lived with them, the book presents the life stories of women leaders over the last fifty years, aiming to preserve their contributions for posterity and to inspire young people with moral, ethical, and progressive role models. The book uses African knowledge production strategies that look at the human being holistically, in the prism of Ubuntu, in order to define leadership in Africa from an African perspective, one that celebrates the role of the mother figure and places women at the centre of African values and societal dynamics. This book will be of interest to researchers and students of African studies, gender studies, and Kenyan education and socio-political history"--